Pengaruh Tingkat Pendidikan, Kompetensi, Masa Kerja dan Disiplin Kerja Melalui Motivasi Kerja Terhadap Kinerja Pegawai pada PT. Wirakarya Sakti - Putri, Idfi Diana; Suryani, Arna; Akbar, Ali; Adisetiawan, R. (Universitas Batanghari Jambi, 2024)
This research aims to obtain an overview regarding the level of education, competence, length of service, work discipline, motivation and performance of employees at PT. Wirakarya Sakti and to determine the influence of education level, competency, length of service and work discipline on work motivation and employee performance; and to determine the effect of work motivation on employee performance. The approach used is a combination of descriptive and inferential methods. The population is 1,130 PT employees. Wirakarya Sakti with a sample of 92 respondents. To analyze the data, the Structural Equation Modeling – Partial Least Squares (SEM-PLS) technique was used. The results of this research conclude that the level of education, competency, length of service, work discipline, work motivation and employee performance at PT. Wirakarya Sakti is in quite high condition. Apart from that, the level of education, competency, length of service and work discipline have a positive and significant influence on work motivation and employee performance at PT. Wirakarya Sakti. Likewise, work motivation has a positive and significant influence on employee performance.